International Study of Comparative Health Effectiveness with Medical and Invasive Approaches- Chronic Kidney Disease (ISCHEMIA-CKD): Rationale and Design - Bangalore, Sripal (Am Heart J, 2018)
BACKGROUND: Patients with chronic kidney disease (CKD) and stable ischemic heart disease (SIHD) are at markedly increased risk of cardiovascular events. Prior trials comparing a strategy of optimal medical therapy (OMT) with or without revascularization have largely excluded patients with advanced CKD. Whether a routine invasive approach when compared with a conservative strategy is beneficial in such patients is unknown. METHODS: ISCHEMIA-CKD is a National Heart, Lung, and Blood Institute-funded randomized trial designed to determine the comparative effectiveness of an initial invasive strategy (cardiac catheterization and optimal revascularization (percutaneous coronary intervention [PCI] or coronary artery bypass graft surgery [CABG], if suitable), plus OMT) versus a conservative strategy (OMT alone, with cardiac catheterization and revascularization [PCI or CABG, if suitable] reserved for failure of OMT) on long-term clinical outcomes, in 777 patients with advanced CKD (defined as those with estimated glomerular filtration rate [eGFR] <30 ml/min/1.73m(2) or on dialysis) and moderate or severe ischemia on stress testing. Participants were randomized in a 1:1 fashion to the invasive or a conservative strategy. The primary endpoint is a composite of death or nonfatal myocardial infarction (MI). Major secondary endpoints are a composite of death, nonfatal MI, hospitalization for unstable angina, hospitalization for heart failure, or resuscitated cardiac arrest; angina control and disease-specific quality of life. Safety outcomes such as initiation of maintenance dialysis and a composite of initiation of maintenance dialysis or death will be reported. The trial is projected to have 80% power to detect a 22% to 24% reduction in the primary composite endpoint with the invasive strategy when compared with the conservative strategy. CONCLUSIONS: ISCHEMIA-CKD will determine whether an initial invasive management strategy improves clinical outcomes when added to OMT in patients with advanced CKD and SIHD.